Choosing social-educational professions in post-soviet countries: international comparison - Aiste Urboniene (Social Work & Society, 2004)
The motivation functions as the most important and decisive factor in choosing the profession Therefore it has an especially remarkable role in the further professional activity of a social-educational worker to raise one's qualification and progress as a specialist. The issue of the professional motivation for choosing social-educational work-studies is becoming increasingly important in post-soviet countries, where the institution of social worker is new and the social exclusion is so widely expressed. The issue of the professional aptitude of students is also important in various professional fields, however in social-educational professions it's importance is exceptional. The profession of social-educational work is based on competences that are constantly expanding and becoming more and more complex.